N‐phosphorylated Iminophosphoranes based on 9, 10‐Dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide and their flame‐retardant behavior in epoxy resins. Issue 9 (14th September 2020) - Weinert, Michael; Döring, Manfred
Abstract: Two novel N‐phosphorylated iminophosphoranes based on 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) were evaluated as flame retardant (FR) additives. They were incorporated in two different epoxy resin systems (EP) based on diglycidyl ether of bisphenol A (DGEBA) and a novolac glycidyl ether (DEN438) both cured with dicyandiamide/fenuron (D/F). Decomposition temperatures and char yields of the cured EP were evaluated and compared to the corresponding neat EP as well as to structurally related compounds. The flame‐retardant properties were investigated using the UL‐94 V test and further verified with cone calorimetry. The N‐phosphorylated iminophosphoranes with DOPO moieties exhibit distinctive flame‐retardant effects in DGEBA/D/F and DEN438/D/F, depending on the chemical environment around the second phosphorus atom, even with low FR content. If the iminophosphorane is triphenyl phosphite based the mode of action is assigned to act mainly in the condensed phase hence being advantageous in DGEBA/D/F compared to the triphenylphosphine‐based iminophosphorane, which in turn is more active in the gas phase resulting in superiority in DEN438/D/F. Abstract :